Supersonic Flows with Nontraditional Transport Described by Kinetic Methods (Communications in Computational Physics, 2020)
A new class of supersonic nonequilibrium flows is studied on the basis ofsolving the Boltzmann and model kinetic equations with the aim to consider new nonlinear structures in open systems and to study anomalous transfer properties in relaxation zones. The Unified Flow Solver is applied for numerical simulations. Simplegases and gases with inner degrees of freedom are considered. The experimental datarelated to the influence of the so-called optical lattices on the supersonic molecularbeams are considered and numerical analysis of the nonequilibrium states obtainedon this basis is made. The nonuniform relaxation problem with these distributionsis simulated numerically and anomalous transport is confirmed. The conditions forstrong changes of the temperature in the anomalous transfer zones are discussed andare realized in computations.